Preventive Mitigation of Overruns with Project Communication Management and Continuous Learning: PLS-SEM Approach - Yap, Jeffrey Boon Hui; Abdul-Rahman, Hamzah; Wang, Chen (American Society of Civil Engineers, 2018)
Failure to communicate effectively and poor project knowledge continue to plague the construction industry, particularly concerning delay management and cost control. This paper aims to empirically examine the influence of project communication management and project learning as preventive measures to mitigate time-cost overruns. Based on a comprehensive literature review, a conceptual framework was developed. A two-stage data collection was used, namely semistructured interviews and a broad questionnaire survey. The qualitative data was analyzed by content analysis of critical incidents. Partial least-squared based structural equation modeling (PLS-SEM) analyses statistically tested the model hypotheses. The results suggest that project communications and project learning contribute positively to time-cost performance of construction projects. Effective communication tools, critical learning situations, and essential reusable project knowledge are identified. Collective sharing of experiences facilitates personal development and enables effective project learning. A triangulated approach was adopted to conceptualize the control loop-process emphasis on networking and communication, collaborative learning, experience accumulation, and expert judgment as critical elements of continuous learning. As such, this study advances the current knowledge of exploiting project communication management and project learning in mitigating time-cost overruns in construction.